Future entrepreneurs: who are they? - Zagorodnya, Tetiana; Harkusha, Olena O. (My University, 2019)
Generation Z has a set of social characteristics that make them completely different from people from other generations. To avoid “conflicts of generations” and to build adequate and productive cooperation, it is necessary to find out the main features of the modern generation. That is the main idea of our article.
Keywords: entrepreneurs; generation Z; characteristics; підприємці; покоління Z; характерні особливості; кафедра ділової іноземної мови та міжнародної комунікації